Three leafhoppers newly recorded from the European mainland (Hemiptera: Auchenorrhyncha: Cicadellidae), with notes on their habitats - Avivar-Lozano, Laura; Pérez-Guerrero, Sergio; Molina-Rodríguez, José Mª; Reis, Fabio; Aguin-Pombo, Dora (Zootaxa, 2024)
The leafhopper fauna of the Iberian Peninsula is the least studied in Europe. Recent surveys in agroecosystem areas of southern Spain, specifically in Andalusia, aimed to identify potential Auchenorrhyncha vectors of the bacterium Xylella fastidiosa. During these surveys, three previously unrecorded species of Cicadellidae belonging to the subfamily Deltocephalinae have been discovered. These newly recorded species are Balclutha incisa (Matsumura), Cicadulina (Cicadulina) bipunctata (Melichar), and Maiestas angustisecta (Linnavuori). Generally, these species were previously only known from American, African and eastern Palaearctic regions. This work is the first to record these species on the European mainland. Detailed descriptions of adult specimens have been provided, along with information on their current distribution and host plants. The potential role of these leafhoppers as potential vectors of plant pathogens is discussed, highlighting their importance in agroecosystems.